OPTIMUM POWER FOR ER-70S-2 AND SS400 DISSIMILAR CDW JOINT - Darmadi, Djarot B.; Gapsari, Femiana; Dirman, Steamy Renergia; Talice, Marco (Journal of Applied Engineering Science, 2023)
Selecting the right cutting tool material for the type of workpiece material plays a very important role in the machining process. The efficiency of the machining process is greatly influenced by this selection. The tables in the manuals or the manufacturer's instructions are commonly used documents for the selection of cutting tool materials. Within each of these document types, the cutting tool materials were described by different criteria. So, tool selection is considered as a multi-criteria decision-making activity. The values of the criteria for each type of cutting tool can be a number or a certain range. This study proposes a new method to rank and select cutting tools. First, a ranking of the solutions for each criterion will be performed. This ranking is based on the mean value of the criteria in each solution. Therefore, this method is called “Ranking the Solutions based on the Mean Value of Criteria - RSMVC”. The RSMVC method was proven to be a highly reliable method for ranking the cutting tool materials. These results were successfully verified when solving the problems in different cases of cutter material selection.
Keywords: capacitive discharge welding, dissimilar metal welding joints, SCC resilience, SCC susceptibility, stress corrosion cracking